Seasons [videorecording (DVD)] - Cluzaud, Jacques; Perrin, Jacques, 1941- (Music Box Films, 2016)
After traveling the world alongside migrating birds and diving the oceans with whales and manta rays, Jacques Perrin and Jacques Cluzaud return to more familiar ground: the lush green forests and megafauna that emerged across Europe following the last Ice Age.